Electronic Conductive Inorganic Cathodes Promising High‐Energy Organic Batteries. Issue 8 (20th January 2021) - Mao, Minglei; Wang, Shu; Lin, Zejing; Liu, Tao; Hu, Yong‐Sheng; Li, Hong; Huang, Xuejie; Chen, Liquan; Suo, Liumin
Abstract: The electrochemical utilization of organic electrode materials (OEMs) is highly dependent on an excess amount of inactive carbon at the expense of low packing density and energy density. In this work, the challenges by substituting inactive carbon with electronic conductive inorganic cathode (ECIC) materials, which are endowed with high electronic conductivity to transport electrons for redox reactions of the whole electrodes, high ion‐storage capacity to act as secondary active materials, and strong affinity with OEMs to inhibit their dissolution, are addressed. Combining representative ECICs (TiS2 and Mo6 S8 ) with organic electrode materials (perylene‐3, 4, 9, 10‐tetracarboxylic dianhydride (PTCDA) and hexaazatrinaphthalene (HATN)) simultaneously achieves high capacity, low porosity, lean electrolyte, and thus high energy density. High gravimetric and volumetric energy densities of 153 Wh kg −1 and 200 Wh L −1 are delivered with superior cycling stability in a 30 mA h‐level Li/PTCDA‐TiS2 pouch cell. The proof‐of‐concept of organic–ECIC electrodes is also successfully demonstrated in monovalent Na, divalent Mg, and trivalent Al batteries, indicating their feasibility and generalizability. With the discovery of more ECIC materials and OEMs, it is anticipated that the proposed organic–ECIC system can result in further improvements at cell level to compete with transition metal‐based Li‐ion batteries. Abstract : The excessive inactive carbon in organic electrode materials (OEMs) is substituted by electronic conductive inorganic cathode materials, which are endowed with high electronic conductivity to transport electrons, high ion‐storage capacity to act as secondary active materials, as well as strong affinity to OEMs. The strategy simultaneously achieves high capacities, low porosity, lean electrolyte, and thus high energy densities.